Positive electrode active material for rechargeable lithium-ion batteries

A single crystal positive electrode active material with controlled Al and B content enhances the initial discharge capacity and reduces irreversible capacity in lithium-ion batteries, addressing the limitations of existing NMC-based materials.

JP7620108B2Active Publication Date: 2025-01-22UMICORE(BE)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023536165
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-15
Filing Date
2021-12-14
Publication Date
2025-01-22
Estimated Expiration
2041-12-14

AI Technical Summary

Technical Problem

Existing positive electrode active materials for rechargeable lithium-ion batteries have low initial discharge capacity (DQ1) and high irreversible capacity (IRRQ), particularly those containing lithium nickel manganese cobalt oxide (NMC) with a high nickel content.

Method used

A single crystal positive electrode active material powder containing Al and B elements, with specific compositional ratios of nickel, cobalt, manganese, and trace amounts of other metals, is developed to enhance DQ1 and reduce IRRQ, achieved by precise control of elemental ratios and crystal morphology.

Benefits of technology

The single crystal powder achieves higher DQ1 and lower IRRQ, with DQ1 exceeding 215 mAh/g and IRRQ below 9.5% when the nickel content is above 70 mol%, demonstrating improved electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620108000009
    Figure 0007620108000009
  • Figure 0007620108000010
    Figure 0007620108000010
  • Figure 0007620108000011
    Figure 0007620108000011
Patent Text Reader

Abstract

A positive electrode active material for a battery containing Li, M', and oxygen, wherein M' contains Ni with a content a of 70.0 mol% to 95.0 mol%, Co with a content x of 0.0 mol% to 25.0 mol%, Mn with a content y of 0.0 mol% to 25.0 mol%, a dopant D with a content z of 0.0 mol% to 2.0 mol%, and Al and B with a total content c of 0.1 mol% to 5.0 mol%, and the active material contains Al with an Al content of Al A and B content B A With a, x, y, z, c, Al A and B A is measured by ICP, and Al A and B A is expressed as a mole fraction relative to the sum of a, x, and y, and the positive electrode active material has an average Al fraction Al as measured by XPS analysis. B and average B fraction B B The ratio of Al B / Al A >1.0, and the ratio B B / B A >1.0, and the positive electrode active material is a single crystal powder.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cathode active material for rechargeable lithium-ion batteries. More specifically, the present invention relates to a particulate cathode active material comprising Al and B elements; a battery comprising the particulate cathode active material comprising Al and B elements; and the use of the cathode active material in any one of the following batteries: a portable computer, a tablet, a mobile phone, an electric vehicle, and an energy storage system. [Background technology]

[0002] The present invention relates to a monocrystalline positive electrode active material powder for rechargeable lithium-ion batteries (LIBs), comprising the elements Al and B.

[0003] A positive electrode active material containing Al and B elements is already known, for example from US 2016 / 336595. US 2016 / 336595 discloses a positive electrode active material powder made from a mixture of Lithium Nickel Manganese Cobalt Oxide (NMC) powder, Al(OH)3 powder and B2O3 powder heated to 400°C. The Ni content in NMC is about 60 mol%. However, the positive electrode active material according to US 2016 / 336595 has a low initial discharge capacity (DQ1) and a high irreversible capacity (IRRQ).

[0004] Therefore, the object of the present invention is to provide a cathode active material having a higher DQ1 and a lower IRRQ than known materials. In particular, the object of the present invention is to provide a cathode active material having a DQ1 higher than 215.0 mAh / g and an IRRQ lower than 9.5% when the molar ratio of Ni to M' obtained by the analytical method of the present invention is higher than 80 mol%, and a DQ1 of at least 185 mAh / g and an IRRQ lower than 12% when the molar ratio of Ni to M' obtained by the analytical method of the present invention is at least 70 mol%. Summary of the Invention

[0005] The object is to provide a cathode active material for a rechargeable lithium ion battery, the cathode active material being a powder, the cathode active material comprising Li, M', and oxygen, M' being: Ni with a content a of 70.0 mol% to 95.0 mol% relative to M'; Co with a content x of 0.0 mol% to 25.0 mol% relative to M'; Mn with a content y of 0.0 mol% to 25.0 mol% relative to M'; D having a content z of 0.0 mol% to 2.0 mol% relative to M', D containing at least one element selected from the group consisting of Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, Zn, W, and Zr; Al and B, wherein the total content c of Al and B is 0.1 mol% to 5.0 mol% relative to M'; a, x, y, z and c are measured by ICP; a+x+y+c+z is 100.0 mol%, The positive electrode active material contains Al A and B content B A Al A and B. A was determined by ICP analysis, and Al A and B. A is expressed as a mole fraction compared to the sum of a, x, and y, When the powder is measured by XPS analysis, the average Al fraction Al B and average B fraction B B indicates Al B and B. B is expressed as a mole fraction compared to the sum of the fractions of Co, Mn and Ni, as measured by XPS analysis, Relative Al B / Al A > 1.0, Ratio B B / B A > 1.0, This is accomplished by providing a cathode active material, wherein the powder is a single crystal powder.

[0006] It is indeed observed that higher DQ1 and lower IRRQ are achieved using the cathode active materials according to the present invention, as illustrated by the examples and supported by the results provided in Table 3.

[0007] Furthermore, in a first aspect, the present invention provides an electrochemical cell comprising an active cathode material according to the first aspect of the invention, in a second aspect, the present invention provides a battery cell comprising an active cathode material according to the first aspect of the invention, and in a third aspect, the present invention provides the use of an active cathode material according to the first aspect of the invention in a battery.

[0008] For further guidance and to better understand the teachings of the present invention, the drawings are included, which are intended to aid in the explanation of the invention and are not intended to limit the invention disclosed herein. [Brief description of the drawings]

[0009] [Figure 1] 1 shows a scanning electron microscope (SEM) image of a positive electrode active material powder of EX4 having a single crystal morphology. [Figure 2a] 1 shows a comparison of DQ1 for examples and comparative examples as a function of nickel content in the positive electrode active material. [Figure 2b] 1 shows a comparison of IRRQ for Examples and Comparative Examples as a function of nickel content in the positive electrode active material. [Figure 3a] The XPS spectrum of EX4.2 measured in the range of 66 to 80 eV including the Al2p and Ni3p peaks is shown. [Figure 3b] The XPS spectrum of EX4.2 measured in the range of 187 to 197 eV including the Bls peak is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Unless otherwise defined, all terms used in disclosing the present invention, including technical and scientific terms, have the meanings commonly understood by those skilled in the art to which the present invention belongs. With further guidance, definitions of terms are included to better understand the teachings of the present invention. As used herein, the following terms have the following meanings: The recitation of numerical ranges by endpoints includes all numbers and fractions subsumed within that range as well as the recited endpoints. All percentages are understood to be percent by weight, abbreviated as "wt. %," unless otherwise defined or a different meaning is apparent to one of ordinary skill in the art from its usage and in the context in which it is used.

[0011] As used herein, "about" referring to a measurable value, such as a parameter, amount, length of time, and the like, is meant to encompass a variation of no more than ±20%, preferably no more than ±10%, more preferably no more than ±5%, even more preferably no more than ±1%, and even more preferably no more than ±0.1% of the specified value or from the specified value, to the extent that such variations are appropriate for the practice of the disclosed invention, although it is to be understood that the value to which the "about" modifier refers is itself specifically disclosed.

[0012] The term "ppm" as used herein means parts per million by mass.

[0013] The term "median particle size D50", as defined herein, can be used interchangeably with the term "D50" or "d50" or "median particle size" or "median particle size (d50 or D50)". D50 is defined herein as the particle size at 50% of the cumulative volume percent distribution. D50 is typically determined by laser diffraction particle size analysis.

[0014] As defined herein, the term "at%" is equivalent to the term "atomic percent" and represents atomic percentage. The term "at%" of a given element expressing a concentration means what percentage of the total atoms in the compound are atoms of that element. The term "at%" is equivalent to the term "mol%" or "mole percent."

[0015] The positive electrode active material is defined as a material that is electrochemically active in the positive electrode, which is understood to be a material that can capture and release Li-ions when exposed to a voltage change for a certain period of time.

[0016] positive electrode active material In a first aspect, the present invention provides an active cathode material for a rechargeable lithium ion battery, the active cathode material being a powder, the active cathode material comprising Li, M′, and oxygen, wherein M′ is Ni with a content a of 70.0 mol% to 95.0 mol% relative to M'; Co with a content x of 0.0 mol% to 25.0 mol% relative to M'; Mn with a content y of 0.0 mol% to 25.0 mol% relative to M'; D having a content z of 0.0 mol% to 2.0 mol% relative to M', D containing at least one element selected from the group consisting of Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, Zn, W, and Zr; Al and B, where the total content c of Al and B is 0.1 mol% to 5.0 mol% relative to M', and a, x, y, z and c are measured by ICP; a+x+y+c+z is 100.0 mol%, The positive electrode active material contains Al A and B content B A Al A and B. A was determined by ICP analysis, and Al A and B. A is expressed as a mole fraction compared to the sum of a, x, and y, When the powder is measured by XPS analysis, the average Al fraction Al B and average B fraction B B indicates Al B and B. B is expressed as a mole fraction compared to the sum of the fractions of Co, Mn and Ni, as measured by XPS analysis, Relative Al B / Al A >1, and the ratio B B / B A >1, A positive electrode active material is provided, wherein the powder is a single crystal powder.

[0017] The single crystal powder has a size of at least 45 μm by at least 60 μm (i.e., at least 2700 μm) in the SEM image. 2 of 100 μm×100 μm (i.e., at least 10,000 μm 2 It is believed that the powder has 80% or more of the particles within a field of view having a single crystal morphology.

[0018] A particle is considered to have a single crystal morphology if it is composed of only one, or very few, constituent particles, at most five, as viewed by SEM or TEM. For example, FIG. 1, an SEM image of EX4, shows particles with a single crystal morphology.

[0019] In determining the single crystal morphology of a particle, particles having a maximum linear dimension observed by SEM that is smaller than 20% of the powder median particle size D50 as determined by laser diffraction are ignored. This avoids particles that are single crystal in nature but may have a number of other very small particles attached to them being erroneously considered not to have single crystal morphology.

[0020] The positive electrode active material for rechargeable lithium ion batteries according to the present invention, when used in an electrochemical cell, does have improved electrochemical properties and can achieve higher DQ1 and lower IRRQ, which is illustrated by the examples and the results are shown in Table 3.

[0021] XPS analysis provides the atomic content of elements in the top layer of the particle with a penetration depth of about 10.0 nm from the periphery of the particle, which is also referred to as the "surface."

[0022] The composition of the positive electrode active material particles is represented by the general formula Li according to the stoichiometry of the elements determined by known analytical methods such as ICP-OES (inductively coupled plasma-optical emission spectrometry, hereinafter also referred to as ICP) and IC (ion chromatography). 1+b (Ni a Mn y CO x A c D z ) 1-b The ICP analysis provides the weight fraction of elements in the positive electrode active material particles.

[0023] Preferably, the positive electrode active material has a nickel content, a, relative to M', greater than 75.0 mol %, more preferably at least 80.0 mol %, as measured by ICP.

[0024] Preferably, the active cathode material has a cobalt content, x, relative to M', as measured by ICP, of at least 1 mol%, more preferably at least 2 mol%, and even more preferably at least 3 mol%. The present invention provides active cathode materials having a cobalt content, x, relative to M', of 3.0, 5.0, 7.0, 9.0, or 10.0 mol%, or any value therebetween, as measured by ICP.

[0025] Preferably, the active cathode material has a manganese content, y, relative to M', as measured by ICP, of at least 1 mol%, more preferably at least 2 mol%, and even more preferably at least 3 mol%. The present invention provides active cathode materials having a manganese content, y, relative to M', of 3.0, 5.0, 7.0, 9.0, or 10.0 mol%, or any value therebetween, as measured by ICP.

[0026] Preferably, the present invention provides an active cathode material having a molar ratio of lithium to the total molar content of nickel, manganese and / or cobalt such that 0.95≦Li:Me≦1.10, where Me is the total molar fraction of Ni, Mn and / or Co.

[0027] Preferably, the present invention provides an active cathode material according to the first aspect of the present invention, wherein the combined content of Al and B relative to M' is preferably at least 0.1 mol%, more preferably at least 0.4 mol%, relative to M', as measured by ICP. The combined content of Al and B relative to M' is preferably at most 2.0 mol%, as measured by ICP.

[0028] Preferably, the positive electrode active material of the present invention contains Al, B and W each in a content of at least 0.02 mol % relative to M' as measured by ICP.

[0029] Preferably, Al A is between 0.025 mol % and 2.0 mol %, as measured by ICP, and is expressed as a mole fraction relative to the sum of a, x, and y.

[0030] Preferably, B A is between 0.025 mol % and 2.0 mol %, as measured by ICP, and is expressed as a mole fraction relative to the sum of a, x, and y.

[0031] Preferably, the positive electrode active material of the present invention has a W content W A W A is determined by ICP analysis and expressed as a mole fraction relative to the sum of a, x, and y, and the average W fraction W B indicates W B is expressed as a mole fraction compared to the sum of the fractions of Co, Mn and Ni, as measured by XPS analysis, and the ratio W B / W A >1.0.

[0032] Preferably, W Ais between 0.025 mol % and 2.0 mol %, as measured by ICP, and is expressed as a mole fraction relative to the sum of a, x, and y.

[0033] Preferably, B A is at least 0.0009, in other words at least 0.09 mol %, as measured by ICP, and more preferably B A is at least 0.0018, in other words at least 0.18 mol %, expressed as a mole fraction compared to the sum of a, x and y.

[0034] Preferably, Al A is at most 0.008, in other words at most 0.8 mol %, as measured by ICP, expressed as a mole fraction compared to the sum of a, x and y.

[0035] In a preferred embodiment, ·Comparison with Al B / Al A <800, and / or ·Ratio B B / B A <500.

[0036] In a more preferred embodiment, ·Comparison with Al B / Al A >10, and / or ·Ratio B B / B A >10.

[0037] In an even more preferred embodiment, ·Comparison with Al B / Al A >150, and / or ·Ratio B B / B A >100.

[0038] Preferably, the ratio W B / W A >10, more preferably, the ratio W B / W A >50, most preferably, ratio WB / W A >115.

[0039] In a preferred embodiment, the ratio W B / W A <500.

[0040] Preferably, the present invention provides a cathode active material according to the first aspect of the present invention, wherein the cathode active material has a median particle size (d50 or D50) of 2.0 μm to 9.0 μm as determined by laser diffraction. The median particle size (d50 or D50) can be measured using a Malvern Mastersizer 3000.

[0041] Preferably, the median particle size is from 2.0 μm to 8.0 μm, more preferably from 3.0 μm to 7.0 μm, and most preferably about 4.0 μm.

[0042] Preferably, the present invention provides a cathode active material according to the first aspect of the present invention, the cathode active material having a DQ1 of at least 215 mAh / g and an IRRQ of up to 9.5% when the molar ratio of Ni to M' is greater than 80 mol%, more preferably, the cathode active material has a DQ1 of at least 185 mAh / g and an IRRQ of up to 12% when the molar ratio of Ni to M' is between 70 mol% and 75 mol%. The DQ1 and IRRQ are determined by coin cell test procedures using a 1C current definition of 220 mAh / g when the molar ratio of Ni to M' is greater than 80 mol%, and using a 1C current definition of 160 mA / g in the 4.4 to 3.0 V / Li metal window range. The test procedures are further described in § 1.3 and are incorporated herein by reference.

[0043] Preferably, the cathode active material according to the first aspect of the present invention comprises LiAlO2, Al2O3, and Li-BO compounds identified by XPS.

[0044] Electrochemical Cell In a second aspect, the present invention provides a battery cell comprising an active cathode material according to the first aspect of the present invention.

[0045] In a third aspect, the present invention provides the use of the cathode active material according to the first aspect of the present invention in a battery of any one of a portable computer, a tablet, a mobile phone, an electric vehicle, and an energy storage system. EXAMPLES

[0046] The following examples are intended to further clarify the invention, but are not intended to limit the scope of the invention.

[0047] 1. Description of analysis method 1.1.Inductively Coupled Plasma The composition of the positive electrode active material powder is measured by inductively coupled plasma (ICP) method using an Agilent 720 ICP-OES (Agilent Technologies, https: / / www.agilent.com / cs / library / brochures / 5990-6497EN%20720-725_ICP-0ES_LR.pdf). One gram of powder sample is dissolved in 50 mL of high-purity hydrochloric acid (at least 37 wt% HCl with respect to the total weight of the solution) in an Erlenmeyer flask. The flask is covered with a watch glass and heated on a hot plate at 380 °C until the powder is completely dissolved. After cooling to room temperature, the solution from the Erlenmeyer flask is poured into a first 250 mL volumetric flask.

[0048] The first volumetric flask is then filled to the 250 mL mark with deionized water, followed by a complete homogenization step (first dilution). An appropriate amount of solution is pipetted from the first volumetric flask and transferred to a second 250 mL volumetric flask for the second dilution, and the second volumetric flask is filled to the 250 mL mark with internal standard elements and 10% hydrochloric acid, followed by homogenization. Finally, this solution is used for ICP measurements.

[0049] 1.2.Particle size distribution The particle size distribution (PSD) of the cathode active material powders is measured by laser diffraction particle size analysis by dispersing each of the powder samples in aqueous media using a Malvern Mastersizer 3000 equipped with a Hydro MV wet dispersion accessory (https: / / www.malvernpanalytical.com / en / products / product-range / mastersizer-range / mastersizer-3000#overview). Sufficient ultrasonic irradiation and stirring are applied and appropriate surfactants are introduced to improve the dispersion of the powders. D50 is defined as the particle size at 50% of the cumulative volume percent distribution obtained from the Malvern Mastersizer 3000 by Hydro MV measurements.

[0050] 1.3.Coin Cell Test 1.3.1. Preparation of Coin Cells ·Preparation of coin cells for CEX1, EX1.1, EX1.2, CEX2, EX2.1, EX2.2, CEX3, EX3.1, EX3.3. For the preparation of the positive electrode, a slurry containing positive active material powder, conductor (Super P, Timcal), and binder (KF#9305, Kureha) in a solvent (NMP, Mitsubishi) with a weight ratio of 96.5:1.5:2.0 is prepared by a high-speed homogenizer. The homogenized slurry is spread on one side of an aluminum foil using a doctor blade coater with a gap of 170 μm. The foil coated with the slurry is dried in an oven at 120°C and then pressed using a calender tool with a gap of 10 μm.

[0051] It is then dried again in a vacuum oven to completely remove the residual solvent in the electrode film. The coin cell is assembled in an argon-filled glove box. A separator (Celgard2320) is placed between the positive electrode and the lithium foil used as the negative electrode. 1M LiPF6 in EC / DMC (1:2) is used as the electrolyte and dropped between the separator and the electrode. The coin cell is then completely sealed to prevent electrolyte leakage.

[0052] Preparation of coin cells for CEX4, EX4.1, EX4.2, CEX5.1, and CEX5.2 For the preparation of the positive electrode, a slurry containing the positive electrode active material powder, conductor (Super P, Timcal), and binder (KF#9305, Kureha) in a ratio of 90:5:5 by weight in a solvent (NMP, Mitsubishi) is prepared by a high-speed homogenizer. The homogenized slurry is spread onto one side of an aluminum foil using a doctor blade coater with a gap of 230 μm. The foil coated with the slurry is dried in an oven at 120° C. and then pressed using a calender tool with a gap of 40 μm.

[0053] It is then dried again in a vacuum oven to completely remove the residual solvent in the electrode film. The coin cell is assembled in an argon-filled glove box. A separator (Celgard2320) is placed between the positive electrode and the lithium foil used as the negative electrode. 1M LiPF6 in EC / DMC (1:2) is used as the electrolyte and dropped between the separator and the electrode. The coin cell is then completely sealed to prevent electrolyte leakage.

[0054] Test Method The test method is a conventional "fixed cut-off voltage" test. Conventional coin cell testing in this invention follows the schedule shown in Table 1. Each cell is cycled at 25°C using a Toscat 3100 computer controlled galvanostatic cycling station (Toyo, http: / / www.toyosystem.com / image / menu3 / toscat / TOSCAT-3100.pdf).

[0055] The 1C current definition is 220mAh / g for CEX1, EX1.1, EX1.2, CEX2, EX2.1, EX2.2, CEX3, EX3.1, and EX3.3, and 160mAh / g for CEX4, EX4.1, EX4.2, CEX5.1, and CEX5.2. The initial charge capacity (CQ1) and discharge capacity (DQ1) are measured in constant current mode (CC) at a C-rate of 0.1C in the range of 4.3V to 3.0V / Li metal window.

[0056] The irreversible capacity IRRQ is expressed as a percentage as follows:

[0057]

number

[0058] [Table 1]

[0059] 1.4.X-ray photoelectron spectroscopy (XPS) In the present invention, X-ray photoelectron spectroscopy (XPS) is used to analyze the surface of the positive electrode active material powder particles. In the XPS measurement, the signal is obtained from the top of the sample, i.e., the first few nanometers (e.g., 1 nm to 10 nm) of the surface layer. Therefore, all elements measured by XPS are contained in the surface layer.

[0060] For the surface analysis of the positive electrode active material powder particles, XPS measurements are performed using a Thermo K-α+ spectrometer (Thermo Scientific, https: / / www.thermofisher.com / order / catalog / product / IQLAADGAAFFACVMAHV). Monochromatic Al Kα radiation (hu=1486.6 eV) is used with a spot size of 400 μm and a measurement angle of 45°. A broad survey scan to identify the elements present on the surface is performed with a pass energy of 200 eV. The C1s peak with maximum intensity (or center) at a binding energy of 284.8 eV is used as the calibration peak position after data collection. Then, for each identified element, at least 10 precise narrow scans at 50 eV are performed to determine the exact surface composition.

[0061] Curve fitting is performed with CasaXPS Version 2.3.19PR1.0 (Casa Software, http: / / www.casaxps.com / ) using Shirley type background processing and Scofield sensitivity coefficients. Fitting parameters are according to Table 2a. Line shape GL(30) is the Gaussian / Lorentzian product formula with 70% Gaussian and 30% Lorentzian lines. LA(α,β,m) is the asymmetric line shape, where α and β define the tail broadening of the peak and m defines the width.

[0062] [Table 2]

[0063] For the Al, B, Co, and W peaks, constraints are set for each peak defined according to Table 2b. Ni3p and W5p3 are not quantified.

[0064] [Table 3]

[0065] Table 2c shows the criteria for the maximum peak intensity position range of Al and B related compounds.

[0066] [Table 4]

[0067] *The range of binding energies of Al peak 1 varies with the amount of Al doped in the structure.

[0068] The surface contents of Al, B, and W measured by XPS are expressed as the mole fraction of Al, B, and W, respectively, in the surface layer of the particle divided by the combined content of Ni, Mn, and Co in that surface layer, and are calculated as follows:

number

[0069] 2. Examples and Comparative Examples Comparative Example 1: A single crystal positive electrode active material, designated CEX1, is prepared according to the following steps.

[0070] Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.86 Mn 0.07 Co 0.07 Nickel-based transition metal oxide hydroxide powder (TMH1) having the formula (I) is prepared by co-precipitation in a large-scale continuous stirred tank reactor (CSTR) with mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia.

[0071] Step 2) Heating: The TMH1 prepared in step 1) is heated at 400° C. for 7 hours in an oxidizing atmosphere to obtain a heated powder.

[0072] Step 3) First mixture: The heated powder prepared in step 2) is mixed with LiOH in an industrial blender to obtain a first mixture having a lithium to metal (Ni, Mn and Co) ratio of 0.96.

[0073] Step 4) First calcination: The first mixture from step 3) is calcined at 890° C. for 11 hours in an oxidizing atmosphere to obtain a first calcined powder.

[0074] Step 5) Wet bead milling: To obtain a milled powder, the first calcined powder from step 4) is bead milled in a solution containing 0.5 mol% Co with respect to the total molar content of Ni, Mn, and Co in the first calcined powder, followed by drying and sieving steps. The weight ratio of bead milled solid to solution is 6:4 for 20 minutes.

[0075] Step 6) Second Mixing: To obtain a second mixture, the milled powder obtained from step 5) is mixed in an industrial blender with 1.5 mol % Co from CO3O4, 0.25 mol % Zr from ZrO2, and 7.5 mol % Li from LiOH with respect to the total molar content of Ni, Mn, and Co in the milled powder, respectively.

[0076] Step 7) Second calcination: The second mixture from step 6) is calcined at 760° C. for 10 hours in an oxidizing atmosphere, followed by a milling and sieving step with alumina (Al2O3) powder. The sieved powder containing 250 ppm Al is designated CEX4. The powder has a median particle size of about 4 μm as determined by laser diffraction measured on a Malvern Mastersizer 3000.

[0077] Example 1 EX1.1 is prepared according to the following process.

[0078] Step 1) Mixing: CEX1 is mixed with H3BO3 powder in an industrial blender to obtain a mixture containing 500 ppm B.

[0079] Step 2) Calcination: The mixture from step 1) is calcined at 375°C for 7 hours in an oxidizing atmosphere, followed by a grinding and sieving step. The product from this step is a ground powder labeled EX1.1.

[0080] Alumina powder in an amount of 250-1000 ppm Al based on the total weight of the final product can be added in the grinding and sieving process of step 2) as a free-flowing agent to aid in the sieving process.

[0081] EX1.2 is prepared according to the same method as EX1.2, except that in step 1), WO3 powder is added together with CEX1 to obtain a mixture containing 500 ppm B and 4500 ppm W.

[0082] Comparative Example 2 A single crystal positive electrode active material, designated CEX2, is prepared according to the following steps.

[0083] Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.90 Mn 0.05 Co 0.05 A nickel-based transition metal oxide hydroxide powder (TMH2) having the formula: is prepared by co-precipitation in a large-scale continuous stirred tank reactor (CSTR) with mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. Step 2) First mixture: The TMH2 prepared in step 2) is mixed with LiOH in an industrial blender to obtain a first mixture having a lithium to metal (Ni, Mn, and Co) ratio of 0.96.

[0084] Step 3) First calcination: The first mixture from step 2) is calcined at 890° C. for 11 hours in an oxidizing atmosphere to obtain a first calcined powder.

[0085] Step 4) Wet bead milling: To obtain a milled powder, the first calcined powder from step 3) is bead milled in a solution containing 0.5 mol% Co with respect to the total molar content of Ni, Mn, and Co in the first calcined powder, followed by drying and sieving steps. The weight ratio of bead milled solid to solution is 6:4.

[0086] Step 5) Second Mixing: To obtain the second mixture, the milled powder obtained from step 4) is mixed with 3.0 mol% Co from CO3O4 with respect to the total molar content of Ni, Mn, and Co in the milled powder in an industrial blender.

[0087] Step 6) Second calcination: The second mixture from step 5) is calcined at 750°C for 12 hours in an oxidizing atmosphere, followed by a milling and sieving step with alumina (Al2O3) powder. The sieved powder containing 250 ppm Al is designated CEX4. The powder has a median particle size of about 3.5 μm as determined by laser diffraction measured on a Malvern Mastersizer 3000.

[0088] Example 2 Prepare EX2.1 following a similar method to EX1.1, except using CEX2 instead of CEX1 in step 1).

[0089] Prepare EX2.2 following a similar method to EX1.2, except using CEX2 instead of CEX1 in step 1).

[0090] Comparative Example 3 In step 10, the metal composition Ni 0.92 Mn 0.05 Co 0.03 Prepare CEX3 according to the same method as CEX2, except that nickel-based transition metal oxide hydroxide powder (TMH3) having the formula (I) is prepared by co-precipitation method.

[0091] Example 3 Prepare EX3.1 following the same method as EX1.1, except using CEX3 instead of CEX1 in step 1).

[0092] Prepare EX3.2 following a similar method to EX1.2, except using CEX3 instead of CEX1 in step 1).

[0093] Comparative Example 4 A single crystal positive electrode active material, designated CEX4, is prepared according to the following steps.

[0094] Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.73 Mn 0.20 Co 0.07 Nickel-based transition metal oxide hydroxide powder (TMH4) having the formula: is prepared by co-precipitation in a large-scale continuous stirred tank reactor (CSTR) with mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. Step 2) First mixture: TMH4 prepared in step 1) is mixed with LiOH in an industrial blender to obtain a first mixture having a lithium to metal (Ni, Mn, and Co) ratio of 1.00.

[0095] Step 3) First calcination: The first mixture from step 2) is calcined at 915° C. for 11 hours in an oxidizing atmosphere to obtain a first calcined powder.

[0096] Step 4) Wet bead milling: To obtain a milled powder, the first calcined powder from step 3) is bead milled in a solution containing 0.5 mol% Co with respect to the total molar content of Ni, Mn, and Co in the first calcined powder, followed by a grinding and sieving step. The weight ratio of the bead milled solid to the solution is 65%.

[0097] Step 5) Second Mixing: To obtain a second mixture, the milled powder obtained from step 4) is mixed in an industrial blender with 2.0 mol % Co from CO3O4 powder, 0.25 mol % Zr from ZrO2 powder, and 8.5 mol % Li from LiOH with respect to the total molar content of Ni, Mn, and Co in the milled powder, respectively.

[0098] Step 6) Second calcination: The second mixture from step 5) is calcined at 775° C. for 12 hours in an oxidizing atmosphere to obtain a second calcined body.

[0099] Step 7) Grinding and sieving: The second calcined body obtained in step 6) is ground with alumina powder and sieved. The sieved powder containing 500 ppm Al is designated CEX4. The powder has a median particle size of 3.5 μm as determined by laser diffraction measured on a Malvern Mastersizer 3000.

[0100] Example 4 EX4.1 is prepared according to the same method as EX1.1, except that in step 1) CEX4 is used instead of CEX1, and in step 2) 500 ppm Al is added from alumina powder. EX4.1 is prepared according to the same method as EX1.2, except that in step 1) CEX4 is used instead of CEX1, and in step 2) 500 ppm Al is added from alumina powder. By wet milling, the above examples and comparative examples are single crystal powders.

[0101] Comparative Example 5 A single crystal positive electrode active material, designated CEX5.1, is prepared according to the following steps.

[0102] Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.68 Mn 0.27 Co 0.05 Nickel-based transition metal oxide hydroxide powder (TMH5) having the above formula is prepared by co-precipitation method in a large-scale continuous stirred tank reactor (CSTR) containing mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia.

[0103] Step 2) First mixture: The TMH5 prepared in step 1) is mixed with LiOH in an industrial blender so as to obtain a first mixture having a lithium to metals (Ni, Mn and Co) ratio of 1.03.

[0104] Step 3) First calcination: The first mixture from step 2) is calcined at 925°C for 10 hours in an oxidizing atmosphere, followed by air jet milling and sieving to obtain the first calcined powder.

[0105] Step 4) Second Mixing: To obtain the second mixture, the milled powder obtained from step 3) is mixed in an industrial blender with 500 ppm Al from Al2O3, 2.0 mol % Co from Co3O4 powder, 0.25 mol % Zr from ZrO2 powder, and 2.0 mol % Li from LiOH, with respect to the total molar content of Ni, Mn, and Co in the milled powder, respectively.

[0106] Step 5) Second calcination: The second mixture from step 4) is calcined at 775° C. for 12 hours in an oxidizing atmosphere to obtain a second calcined body.

[0107] Step 6) Grinding and sieving: The second calcined body obtained in step 5) is ground with alumina powder and sieved. The sieved powder containing 500 ppm Al is designated CEX5.1. The powder has a median particle size of 4 μm as determined by laser diffraction measured on a Malvern Mastersizer 3000.

[0108] By air jet mill pulverization in step 3), CEX5.1 is a single crystal powder.

[0109] Prepare CEX5.2 according to the same method as EX1.1, except using CEX5.1 instead of CEX1 in step 1), calcination time is 9 h, and 500 ppm Al from alumina powder is added in the grinding process in step 2).

[0110] CEX5.2 is based on U.S. Patent Application Publication No. 2016 / 336595.

[0111] [Table 5]

[0112] *When calculated by ICP measurement, M' is the total mole fraction of other elements when analyzed by ICP

[0113] [Table 6]

[0114] *Calculated for the total mole fraction of Ni, Mn, and Co when analyzed by ICP **Calculated relative to the total mole fraction of Ni, Mn, and Co as analyzed by XPS

[0115] Table 3 summarizes the compositions of the examples and comparative examples and their corresponding electrochemical properties. Figures 2a and 2b show the electrochemical properties of Table 3 as a function of the Ni content of the positive electrode active material. In Figures 2a and 2b, it can be clearly seen that the subsequent presence of Al and B is advantageous in increasing DQ1 and decreasing IRRQ of the positive electrode active material having a Ni content of 70 mol% to 95 mol% relative to M'. Furthermore, the subsequent presence of Al, B, and W also increases DQ1 and decreases IRRQ in the same trend as the positive electrode active material containing Al and B compared to the comparative example. EX1.2, EX2.2, and EX3.2 show a further decrease in IRRQ when Al, B, and W may be present together in the positive electrode active material compared to EX1.1, EX2.1, and EX3.1.

[0116] Table 4 summarizes the XPS analysis results of EX1.1 and EX1.2, showing the molar ratios of Al, B, and W relative to the total molar fractions of Ni, Mn, and Co. This table also compares with the ICP analysis results. A molar ratio greater than 0 indicates that Al, B, and W are present on the surface of the positive electrode active material, in relation to the XPS measurement, which obtains the signal from the top of the sample, i.e., the first few nanometers (e.g., 1 nm to 10 nm) of the surface layer. On the other hand, the molar ratios of Al, B, and W obtained in the ICP measurement are obtained from the whole particle. Thus, an XPS to ICP ratio greater than 0 indicates that the element Al, B, or W is mainly present on the surface of the positive electrode active material. For Al and B in EX1.1, and for Al, B, and W in EX2.2 and EX4.2, an XPS to ICP ratio greater than 0 is observed.

[0117] Furthermore, the XPS peak positions are associated with compounds originating from the preparation process. Figure 3a shows the Al peak of EX4.2 overlapping with the Ni3p peak, and Figure 3b shows the Bls peak of EX4.2. Peak deconvolution is performed to separate the contribution of each compound based on the peak position according to the references listed in Table 2c. The contributions of the three different Al-containing compounds and Ni3p are separated Figure 3a, and the result shows that EX4.2 has Al2O3, LiAlO2 and LiAl on the surface. n Me 1-n In Fig. 3b, the B1s peak is deconvoluted into a peak belonging to H3BO3 and another peak with a similar peak position belonging to Li-BO compounds, which can be, but are not limited to, Li2B4O7 and Li4B2O5.

Claims

1. 1. A cathode active material for a rechargeable lithium ion battery, the cathode active material being a powder, the cathode active material comprising Li, M′, and oxygen, wherein M′ is Ni with a content a of 70.0 mol% to 95.0 mol% relative to M'; Co with a content x of 0.0 mol % to 25.0 mol % relative to M'; Mn with a content y of 0.0 mol % to 25.0 mol % relative to M'; D has a content z of 0.0 mol % to 2.0 mol % relative to M', and D contains at least one element from the group consisting of Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, Zn, W, and Zr; Al and B, wherein the total content c of Al and B is 0.1 mol % to 5.0 mol % relative to M'; a, x, y, z and c are measured by ICP; a+x+y+c+z is 100.0 mol%, The positive electrode active material has an Al content of Al A and B content B A and Al A and B A was determined by ICP analysis, and Al A and B A is expressed as a mole fraction compared to the sum of a, x, and y, The powder has an average Al fraction, Al, as measured by XPS analysis. B and average B fraction B B and Al B and B B is expressed as a mole fraction compared to the sum of the Co, Mn and Ni fractions, as measured by XPS analysis; Ratio of Al B / Al A > 1.0, Ratio B B / B A > 1.0, The positive electrode active material, wherein the powder is a single crystal powder.

2. Ratio of Al B / Al A >10, or the ratio Al B / Al A The positive electrode active material according to claim 1, wherein the molecular weight is >150.

3. Ratio of Al B / Al A The positive electrode active material according to claim 1 or 2, wherein Mn is 0.01 to 0.

5.

4. Ratio B B / B A >10, or ratio B B / B A >30, or ratio B B / B A The positive electrode active material according to any one of claims 1 to 3, wherein the positive electrode active material is >100.

5. Ratio B B / B A The positive electrode active material according to any one of claims 1 to 4, wherein the molecular weight is 500 or less.

6. The positive electrode active material according to any one of claims 1 to 5, wherein the positive electrode active material has a W content W A With W A is determined by ICP analysis and expressed as a mole fraction relative to the sum of a, x, and y, and the positive electrode active material has an average W fraction W B indicates W B is expressed as a mole fraction compared to the sum of the fractions of Co, Mn and Ni, as measured by XPS analysis, and the ratio W B / W A > 1.

0.

7. Ratio W B / W A >10, or the ratio W B / W A >50, or the ratio W B / W A The positive electrode active material according to claim 6, wherein the molecular weight is >115.

8. Ratio W B / W A 8. The cathode active material of claim 7, wherein Mn is 0.01 to 0.

5.

9. The cathode active material of any one of claims 1 to 8, wherein the cathode active material has a median particle size D50 of 2.0 μm to 7.0 μm as determined by laser diffraction particle size analysis.

10. The positive electrode active material according to any one of claims 1 to 9, wherein M' contains Al, B and W in an amount of at least 0.02 mol% relative to M' as measured by ICP.

11. The positive electrode active material according to any one of claims 1 to 10, wherein a is greater than 75 mol% relative to M', or a is 80 mol% or greater, as measured by ICP.

12. A battery cell comprising the positive electrode active material according to any one of claims 1 to 11.

13. Use of the positive electrode active material according to any one of claims 1 to 11 in a battery of any one of a portable computer, a tablet, a mobile phone, an electric vehicle, and an energy storage system.

Citation Information

Patent Citations

  • Positive electrode for lithium secondary battery and lithium secondary battery using the same

    JP2012038724A

  • Positive electrode active material for non-aqueous electrolyte secondary battery and method of manufacturing the same

    JP2019192513A

  • Electrode active material, lithium secondary battery containing the electrode active material, and method of preparing the ode active material

    US20180205084A1